Comparison Of Bio-Oil And Synthetic Lubricants Tribological Characters - Ramlan, Nur Diyana (Universiti Sains Malaysia, 2022)
Bio-lubricants have been developed as an alternative to mineral oil-based lubricants because of environmental concerns and the diminishing supply of petroleum. Vegetable oils (red palm oil, soybean oil, coconut oil and sunflower oil) were studied as bio-lubricants and their mixes with anti-wear additives in order to determine their potential usage in car engines. A four-ball tester and pin-on-disc were used to conduct the experiments under ASTM standard. For benchmarking reasons, the performance was compared to that of commercial engine oil. The reduction in friction and wear was negligible when using an equal ratio of vegetable oil and mineral oil. A considerable improvement in friction and wear was seen with the addition of 1% wt of Titanium Dioxide nanoparticles to vegetable oils. Using this addition, the friction coefficient of vegetable oils was comparable to that of a commercial engine oil. Anti-wear agent and friction modifier are all perform by Titanium Dioxide in vegetable oils. In terms of wear-resistance and oxidative stability, the disadvantage of pure vegetable oils is determined to be greater compared to friction when all the data are considered. This effect was pronounced when combined with mineral oils, when their tribological performance predominated. However, using the commercial anti-wear Titanium Dioxide additive, the vegetable oils showed promise as an alternative lubricant for automobile engine systems, despite the fact that there is still considerable room for improvement.